2013
DOI: 10.1590/s0034-737x2013000400009
|View full text |Cite
|
Sign up to set email alerts
|

Severidade de doenças foliares e produtividade de genótipos de milho em resposta à adubação nitrogenada

Abstract: Severity of foliar diseases and genotype maize yield in response to nitrogen fertilizationLeaf diseases, mainly, helmintosporiosis (Bipolaris spp.), anthracnose (Colletotrichum graminicola) and rust (Puccinia spp.), may cause reduction in maize yield. This study aimed to evaluate the occurrence and severity of helmintosporiosis, anthracnose and rust, as well as productivity of different genotypes of maize in response to increasing doses of nitrogen. Disease severity was evaluated using a score scale in nine ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
1
0
5
Order By: Relevance
“…It is a fact that plant responses to pathogens vary from crop to crop depending on the environmental conditions, which are particular to each situation. The work of Santos et al (2013) illustrates this case. The authors found an effect of N doses on the severity of common rust in maize only in one of the years of study, with no record of its occurrence in another year of research.…”
Section: Sources Of N Conventional Tillage Minimum Tillagementioning
confidence: 81%
“…It is a fact that plant responses to pathogens vary from crop to crop depending on the environmental conditions, which are particular to each situation. The work of Santos et al (2013) illustrates this case. The authors found an effect of N doses on the severity of common rust in maize only in one of the years of study, with no record of its occurrence in another year of research.…”
Section: Sources Of N Conventional Tillage Minimum Tillagementioning
confidence: 81%
“…Onde Y i é a severidade na iésima observação; X i é o tempo (dias) na iésima observação e n é o número total de avaliações (21). O índice Tabela 1.…”
Section: Methodsunclassified
“…O milho (Zea mays L.) é uma planta de ciclo anual, pertencente à família Poaceae, adaptada a vários ambientes, consistindo no cereal de maior área de cultivo no mundo (21). No Brasil, o cultivo sucessivo do milho (safra e safrinha), monocultura, irrigação sem critérios técnicos e sistema de plantio direto sem rotação de culturas tem contribuído para o aumento da incidência e severidade de algumas doenças (9).…”
unclassified
“…Dentre os insumos, o nitrogênio é o nutriente mais exigido e absorvido na cultura do milho, sendo essencial para a biossíntese de proteína, enzimas e clorofila, desde os estádios fenológicos iniciais da cultura, promovendo influência direta no crescimento e desenvolvimento, que resulta em incrementos na produtividade (Duete et al, 2008;Santos et al, 2013).…”
Section: Introductionunclassified